Penerapan Komunikasi Pembangunan Di Kabupaten Lebak Melalui Permendagri Nomor 70 Tahun 2019 - Wilansari Wilansari (Magister Komunikasi Universitas Sultan Ageng Tirtayasa, 2022)
This research is to analyze the implementation of the Minister of Home Affairs Regulation no. 70 of 2019 in the Development Planning Process in Lebak Regency and analyze the driving and inhibitory factors. The theory used is the theory of public policy implementation according to Van Metter and Van Horn with six variables, namely: size. and policy, resources, characteristics of implementing agents, attitudes or tendencies of implementers, communication between organizations and implementing activists, and economic, social, and political environments. The research method used is qualitative. The results showed that there are still some obstacles and problems in the Implementation of the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 70 of 2019. among others: (1) The absence of attachments regarding the standardization of data on the needs of local governments; (2) the existence of sectoral egos of the Ministry of Home Affairs who rush to issue SIPD rules and applications; (3) untested application reliability both in structure, content, and network availability.